Analysis of aeromagnetic data over wamba and its adjoining areas in north-central nigeria (2012)
An aeromagnetic intensity contour map of Wamba was acquired, digitised and analysed. The study was aimed at mapping metalliferous mineral deposits in basement rocks, delineating structural lineaments and their trends as well as estimating the depth to magnetic source bodies. Regional- residual separation was applied to a total aeromagnetic intensity contour map to produce a residual aeromagnetic intensity contour map. The rose diagram of the orientations or azimuth direction of the structural lineaments delineated on the maps depicted major trends being NE-SW, NW-SE and NNESSW (Pan-African trends) with minor NNW-SSE and E-W trends (pre-Pan-African trends). Depths to the magnetic source bodies were estimated using Peter's (half-slope) method, indicating two depth source models. The deeper sources ranged from 0.88km to 3.15km and had -32nT to -225nT magnetic intensity, whereas the shallower sources ranged from 0.23km to 0.76km and had -10nT to 20nT magnetic intensity. The deeper sources were most likely due to intra-basement basic intrusive bodies underlying the sediment-covered marginal areas of the Benue Trough. The sedimentary cover in the area was generally low and therefore not likely to favour hydrocarbon generation.